Kewenangan Pemerintah Provinsi Bali dalam Pemberian Perizinan terhadap Usaha Pertambangan Mineral Bukan Logam dan Batuan - Sudharma, I Made; Parsa, I Wayan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 4 (2022)DO - 10.24843/JMHU.2022.v11.i04.p12, 2022)
The purpose of this study is to explain the authority of the Bali Provincial Government in granting non-metallic and rock mineral mining business permits based on the Bali Provincial Regulation Number 4 of 2017 concerning Non-Metal and Rock Mineral Mining Management and the implications arising from the transfer of authority based on Law Number 3 Year 2020 concerning Mineral and Coal Mining. This paper uses normative legal research. The results of the study indicate that there are changes in the leading sector in granting mining permits from the Governor to the Central Government, including: 1) The authority to determine the Mining Business Permit Area (WIUP) and Mining Business Permit (IUP) which is carried out based on the Business Licensing. 2) Authority in fostering and supervising the implementation of mining activities. This authority is delegated to the Provincial Government based on Presidential Regulation Number 55 of 2022 concerning Delegation of Granting Business Licensing in the Mineral and Coal Mining Sector. The implications of the transfer of authority to grant mining permits include: 1) Changing the procedure for obtaining attributive authority to being a delegation in the business licensing model which can be given in the form of standard certificates and permits. 2) The still involvement of the Central Government causes the concept of delegation to reflect the paradigm of centralization in the mining sector. 3) The abolition of the authority of Regency/Municipal Governments in granting permits, supervision, guidance and resolution of community conflicts has created obstacles in mining activities. Tujuan penelitian ini menjelaskan mengenai kewenangan Pemerintah Provinsi Bali dalam memberikan perizinan usaha pertambangan mineral bukan logam dan batuan berdasarkan Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2017 tentang Pengelolaan Pertambangan Mineral Bukan Logam dan Batuan serta implikasi yang ditimbulkan akibat pengalihan kewenangan tersebut berdasarkan Undang-Undang Nomor 3 Tahun 2020 tentang Pertambangan Mineral dan Batubara. Tulisan ini mempergunakan penelitian hukum normatif. Hasil penelitian menunjukkan bahwa adanya perubahan leading sektor pemberian perizinan pertambangan dari Gubernur ke Pemerintah Pusat antara lain: 1) Kewenangan menetapkan Wilayah Izin Usaha Pertambangan (WIUP) dan Izin Usaha Pertambangan (IUP) yang dilaksanakan berdasarkan Perizinan Berusaha. 2) Kewenangan dalam pembinaan serta pengawasan penyelenggaraan kegiatan pertambangan. Kewenangan tersebut didelegasikan kepada Pemerintah Provinsi berdasarkan Peraturan Presiden Nomor 55 Tahun 2022 tentang Pendelegasian Pemberian Perizinan Berusaha di Bidang Pertambangan Mineral dan Batubara. Implikasi pengalihan kewenangan pemberian perizinan pertambangan tersebut antara lain: 1) Merubah tata cara memperoleh kewenangan secara atributif menjadi delegasi dalam model perizinan berusaha yang dapat diberikan dalam bentuk sertifikat standar dan izin. 2) Masih adanya keterlibatan Pemerintah Pusat menyebabkan konsep pendelegasian mencerminkan paradigma sentralisasi pada sektor pertambangan. 3) Dihapuskannya kewenangan Pemerintah Kabupaten/Kota dalam pemberian perizinan, pengawasan, pembinaan dan penyelesaian konflik masyarakat menjadikan hambatan dalam aktivitas pertambangan.